Reliability and Validity of Frontal Plane Kinematics of the Trunk and Lower Extremity Measured With 2-Dimensional Cameras During Athletic Tasks: A Systematic Review With Meta-analysis - Alves Lopes, Thiago Jambo; Ferrari, Deisi; Ioannidis, Joshua; Simic, Milena; De Azevedo, Fabio Micolis [UNESP]; Pappas, Evangelos (J O S P T, 2018)
BACKGROUND: Two-dimensional (2-D) analysis is commonly used to quantify frontal plane kinematics of the trunk and lower extremity. However, there are conflicting results regarding the reliability and validity of these measurements. OBJECTIVE: To synthesize the current literature to determine whether 2-D analysis is a reliable and valid method of measuring frontal plane kinematics of the trunk and lower extremity during squatting, landing, and cutting tasks. METHODS: For this systematic review with meta-analysis, MEDLINE, CINAHL, Embase, Scopus, and SPORTDiscus databases were searched from inception until March 2017. The authors included 16 studies that evaluated the reliability and/or validity of 2-D measurements of frontal plane trunk and/or lower extremity kinematics when compared to 3-D measurements during any of the following tasks: squatting, landing, or cutting. RESULTS: Intrarater reliability (intraday and interday) and interrater reliability of the 2-D video measurements varied from moderate to excellent. In terms of validity, there was poor agreement between the 2-D and 3-D methods, with no correlation between 2-D knee frontal plane projection angle and 3-D knee frontal plane angles (r= 0.127, P=.094) for the single-leg squat, but a moderate to good relationship (r=0.619, P<.001) for the landing task. CONCLUSION: Two-dimensional video analysis of frontal plane trunk and lower extremity kinematics is reliable, but this appears to be dependent on the task and the type of reliability evaluated. The current evidence does not support the use of 2-D video analysis for measuring trunk and lower extremity frontal plane kinematics when accurate measures are required. LEVEL OF EVIDENCE: Diagnosis, level 3. J Orthop Sports Phys Ther 2018;48(10):812-822. Epub 12 Jun 2018. doi:10.2519/jospt.2018.8006
Keywords: 2-D motion; 3-D motion; biomechanics; kinematics; video analysis